Effects of exposure to a 50 Hz sinusoidal magnetic field during the early adolescent period on spatial memory in mice12. Issue 4 (25th January 2013) - Wang, Xiusong; Zhao, Ke; Wang, Dong; Adams, Wendy; Fu, Yu; Sun, Huaying; Liu, Xiaofen; Yu, Hualin; Ma, Yuanye
Abstract Adolescence is a critical developmental stage during which substantial remodeling occurs in brain areas involved in emotional and learning processes. Although a robust literature on the biological effects of extremely low frequency magnetic fields (ELF‐MFs) has been documented, data on the effects of ELF‐MF exposure during this period on cognitive functions remain scarce. In this study, early adolescent male mice were exposed from postnatal day (P) 23–35 to a 50 Hz MF at 2 mT for 60 min/day. On P36–45, the potential effects of the MF exposure on spatial memory performance were examined using the Y‐maze and Morris water maze tasks. The results showed that the MF exposure did not affect Y‐maze performance but improved spatial learning acquisition and memory retention in the water maze task under the present experimental conditions. Bioelectromagnetics 34:275–284, 2013. © 2012 Wiley Periodicals, Inc.